Analisis Interaksi Multi Pihak Dalam Faktor-Faktor Penentu Keberhasilan Pengelolaan keberlanjutan: Perspektif Geopark Musi Rawas Utara - Retnowati, Reni; Mumin, Adhi Tri; Rahmanita, Myrza; Widyastuti, Novita (Multmedia Nusantara Politeknik, 2025)
North Musi Rawas Regency has great potential for sustainable Geopark tourism development. This study analyzes the factors that affect the sustainability of tourism in the North Lake Rayo Musi Rawas Geopark, focusing on the interaction between community involvement, destination components, learning and awareness, and stakeholder collaboration. This study uses a quantitative method with the Partial Least Squares Structural Equation Modeling (PLS-SEM) model to analyze data collected from respondents involved in Lake Rayo Geopark tourism. The results of the study show that community involvement in the destination component, learning and awareness, as well as stakeholder collaboration have a positive and significant influence on the sustainability of Geopark tourism. This research highlights the importance of building strong collaboration between various parties, including communities, local governments, business actors, and community institutions, to achieve responsible, sustainable, and economic, social, and environmental tourism development. In addition, this study also emphasizes the importance of improving the quality of destinations and public awareness of the important value of Geoparks. Improving the quality of destinations can be done through the development of infrastructure and attractive tourist attractions. Meanwhile, increasing public awareness can be done through education, socialization, and promotion about Geoparks and their benefits. This study makes an important contribution to the development of sustainable Geopark tourism in North Musi Rawas Regency. The results of this study can be a guide for stakeholders in formulating effective and sustainable Geopark tourism development policies and strategies.